Respiratory syncytial virus infection in children with acute respiratory infections in Zambia. - Saijo, M. (Cambridge University Press, 1998)
Epidemiological research on respiratory syncytial virus (RSV) infections in children was carried out at the Virology Laboratory, University Teaching Hospital (UTH), in Lusaka, Zambia, from January-December 1996. Specimens including 736 nasal washings and 2424 throat swabs were collected from children with acute respiratory infections (ARI) and tested for RSV by enzyme immunoassay and by virus isolation. RSV was isolated in 62 (4.1%) of 1496 throat swabs collected from March to September and was detected in 99 (16.3%) of 609 nasal washings from March to November. The average RSV isolation rate was 2.6% and the average RSV detection rate was 13.5%. The highest RSV isolation (8.1%) and detection (30.5%) rates were in June 1996. RSV antibody in the 278 serum specimens collected from Zambian children, who were hospitalized in the paediatric ward, UTH, was detected using a standard neutralization test. The antibody positive rate was 60-80% in children > 4 years. It is evident that RSV is one of the main causal agents of ARI in children in Zambia.